Preparation method and application of graphite composite material electrode
By combining fluorinated graphite with phenolic resin, epoxy resin and polyester resin, and adding aluminum and lead metal, graphite composite electrodes are prepared, which solves the problem of short electrode life and achieves excellent electrochemical and mechanical properties , adapt to the needs of a variety of harsh environments.
Patent Information
- Application Number
- CN202411252025.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
AI Technical Summary
The existing electrode materials have short lifespans in electrochemical synthesis, high cost and poor corrosion resistance, insufficient mechanical strength of graphite electrodes, and insufficient electrical conductivity and mechanical strength of composite materials, making it difficult to meet the needs of various harsh environments.
The graphite composite electrode is prepared by ball milling and impregnation treatment by mixing fluorinated graphite with phenolic resin, epoxy resin and polyester resin as filler material, and aluminum and lead metal are added to improve conductivity and mechanical strength, and improved by resin filling. Airtightness and corrosion resistance.
The prepared graphite composite electrode has excellent electrochemical properties, mechanical properties and corrosion resistance, extends its service life and adapts to high temperature and strong corrosion environments.
Smart Images

Figure CN119121280A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemistry, and in particular relates to a preparation method and application of a graphite composite material electrode. Background Art
[0002] Electrochemistry is widely used in energy storage, fuel cells, electrolysis, electroplating, etc. The research of electrochemistry not only improves the efficiency of industrial production, but also provides solutions for sustainable development.
[0003] In the electrochemical synthesis process, the core component is the electrolytic cell, and the ultimate life of the electrolytic cell depends on the life of the electrode material. Electrode materials generally include metal electrodes, graphite electrodes, and composite electrodes. Metal electrodes have good electrical conductivity and mechanical strength, but are more expensive and have poor corrosion resistance; graphite electrodes have good electrical conductivity and corrosion resistance, but have poor machinability and are fragile during assembly. Composite materials have the advantages of easy processing, good corrosion resistance, and good electrical conductivity, but they also have disadvantages such as high air permeability and insufficient mechanical strength.
[0004] Therefore, it is necessary to highly optimize the type and ratio of graphite powder and resin to improve their performance in order to produce a composite material that meets the requirements. In electrochemistry, composite resins have attracted attention due to their excellent mechanical properties, chemical stability and electrical insulation. Common composite resins include epoxy resins, polyurethane resins, phenolic resins, polytetrafluoroethylene and silicone resins.
[0005] Therefore, fluorinated graphite is used as the first conductive filler, and a mixed resin of phenolic resin, epoxy resin and polyester resin is used as a material to fill the pores of fluorinated graphite and solidify therein. Fluorinated graphite is used as a plate material with its excellent conductivity and chemical stability. Phenolic resin can enhance the mechanical strength of the graphite composite plate, epoxy resin can enhance the bonding strength of the graphite composite plate, and polyester resin can enhance the corrosion resistance of the graphite composite plate, so as to adapt to a variety of harsh environments. Summary of the invention
[0006] In order to simultaneously solve the problem of short electrode life, the present invention discloses a method for preparing a graphite composite material and an application of the graphite composite material.
[0007] To achieve the above object, the technical solution of the present invention is as follows:
[0008] First, the present invention provides a method for preparing a graphite composite material electrode, comprising the following steps:
[0009] (1) Pretreatment of graphite fluoride;
[0010] The fluorinated graphite is placed in an oven for drying, the dried fluorinated graphite is placed in a ball mill, and aluminum and lead metal are added for synchronous ball milling and mixing, the rotation speed of the ball mill is 100 to 300 rpm, the ball milling time is 1 to 4 hours, the mass ratio of the grinding medium ceramic ball to the mixed powder is 1 to 5:1, the filling rate of the ball mill drum is 30% to 50%, and a uniformly distributed mixed powder is obtained, and the mixed powder is pressed into a metal fluorinated graphite plate with a thickness of 1 to 5 mm;
[0011] (2) Graphite fluoride and resin mixed and soaked:
[0012] The phenolic resin, epoxy resin and polyester resin are mixed to obtain a glue injection agent; the metal fluoride graphite plate is immersed in the glue injection agent, and after curing, it is washed and dried to obtain a graphite composite material electrode.
[0013] By adopting the above technical solution, the addition of aluminum and lead metals to graphite fluoride can increase conductivity, and aluminum and lead are compatible with graphite fluoride in chemical and physical properties, and usually no adverse reactions will occur after mixing. Graphite fluoride has excellent lubrication properties, and the addition of aluminum and lead can improve the mechanical strength and wear resistance of the mixture. In high temperature or highly corrosive environments, the chemical resistance and high temperature resistance of graphite fluoride can complement the characteristics of aluminum and lead to achieve a better lubrication effect.
[0014] Furthermore, in step (1), the mixed powder is pressed into a metal fluoride graphite plate, specifically comprising the following steps: the sieved mixed powder is weighed in an electronic balance, the weighed mixed powder is placed in a molding tool, first pre-pressed at a pressure of 1 to 2 MPa for 30 seconds to discharge the gas in the powder, and then formally pressed at a pressure of 10 MPa for 10 minutes, and a 1 to 5 mm metal fluoride graphite plate is obtained after demolding. The pressed metal fluoride graphite plate is cut into 50×50 mm plates.
[0015] Furthermore, in step (1), the mass ratio of graphite fluoride, aluminum and lead is 8-9:1-2:1-2.
[0016] Furthermore, in step (1), the content of the fluorinated graphite is 90-99%, preferably 95-99%; and the sheet diameter is 1-10 μm, preferably 5-10 μm.
[0017] Furthermore, in step (2), the mass ratio of the phenolic resin, the epoxy resin, and the polyester resin is 2-5:3-7:2-4.
[0018] Furthermore, in step (2), the impregnation treatment includes the following steps: placing the metal fluoride graphite plate in an impregnation barrel, maintaining the vacuum degree at 0.1 MPa, impregnating for 1 hour, and then adding the injection agent into the impregnation barrel, and maintaining the impregnation pressure at 0.3-0.8 MPa for 40-50 minutes.
[0019] Furthermore, in step (2), curing comprises the following steps: in an argon atmosphere, heating the temperature in a tubular furnace to 300° C. at a heating rate of 3.0 to 5.5° C. / min, and keeping the temperature for 30 minutes.
[0020] Furthermore, the impregnated graphite composite material plate is post-processed to clean the residual mixed resin on the surface, and the cleaned graphite composite material plate is thermally cured.
[0021] By adopting the above technical scheme, when the weight ratio of phenolic resin, epoxy resin and polyester resin is within this range, phenolic resin can enhance the mechanical strength of graphite composite material plate, epoxy resin can enhance the bonding strength of graphite composite material plate, and polyester resin can enhance the corrosion resistance of graphite composite material plate. The mixed resin fills the gap of fluorinated graphite plate and solidifies therein, and is combined with graphite skeleton as a whole, so that the distribution of the overall components of graphite composite material is more uniform and dense, thereby improving the air tightness of plate material. Although the resin is not conductive, the impregnated resin only fills the gap of graphite plate, and will not cut off the conductive path inside the graphite plate material, so it will not have a great impact on the conductive performance of fluorinated graphite plate.
[0022] The graphite composite material electrode prepared by the preparation method of the present invention has excellent electrochemical properties; it also has excellent mechanical properties and corrosion resistance, so that the electrode plate has a long service life.
[0023] By adopting the above technical solution, the graphite composite plate of the present application has excellent electrochemical properties, and the overall mechanical properties of the graphite composite plate are good. The graphite composite plate is not prone to breakage and other problems, and the service life is extended.
[0024] The present invention also provides a graphite composite material electrode prepared by the preparation method as described above.
[0025] The present invention also provides a use of the graphite composite material electrode as described above in an anode plate for electrosynthesis of succinic acid.
[0026] The beneficial effects of the present invention are:
[0027] The present application uses a mixed resin of phenolic resin, epoxy resin and polyester resin with different specific gravities as a modifier to modify fluorinated graphite to obtain a new type of graphite composite material plate; the graphite composite material plate has excellent electrochemical properties, and the graphite with poor mechanical strength is coated with the mixed resin of phenolic resin, epoxy resin and polyester resin, thereby enhancing the mechanical strength and thermal stability of the plate, and effectively reducing electrical corrosion during the electrochemical reaction process, so that the performance of the plate material is durable. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a production process flow chart of the present invention;
[0029] Figure 2 The electrochemical performance test results of application examples 1-5 and comparative example 1 of the present invention are shown;
[0030] Figure 3 The service life test results of the graphite composite material plate prepared in Comparative Example 1 of Examples 1-5 of the present invention;
[0031] Figure 4 The bending strength test results of the graphite composite material plates prepared in Examples 1-5 and Comparative Example 1 of the present invention are shown. DETAILED DESCRIPTION
[0032] The present invention will be further explained below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the following specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0033] Unless otherwise specified, the sources of raw materials for each preparation example, embodiment, and comparative example in this application are as follows:
[0034] Phenolic resin:
[0035] Brand: HY-918, solid content 73-77%, free phenol 10-14%;
[0036] Epoxy resin:
[0037] Brand: E-44, epoxy equivalent 0.41~0.47eq / 100g;
[0038] Polyester resin:
[0039] Brand: 197C, solid content 58-65%, acid value 22-30 mgKOH / g;
[0040] Metal:
[0041] Model: Al, particle size 1mm;
[0042] Model: Pb, particle size 4μm.
[0043] Example 1
[0044] A graphite composite material electric plate, the production process flow chart is as follows Figure 1 As shown, it is prepared according to the following steps:
[0045] (1) Pretreatment of fluorinated graphite: The pretreatment steps of fluorinated graphite are as follows: drying the fluorinated graphite in an oven, placing 270 g of the dried fluorinated graphite in a ball mill, adding 30 g of aluminum and 30 g of lead metal, and performing simultaneous crushing and mixing. The speed of the ball mill is 200 rpm, the grinding time is 1 hour, the grinding medium ratio is 5:1, and the filling rate of the ball mill drum is 50%, ensuring that the obtained mixed powder is evenly distributed. The content of fluorinated graphite is 99%, and the flake diameter is 8 μm.
[0046] The mixed powder was sieved with a 200-mesh sieve and weighed in an electronic balance. The weighed mixed powder was placed in a molding tool and pre-pressed at a pressure of 1 MPa for 30 seconds to discharge the gas in the powder. Then, it was formally pressed at a pressure of 10 MPa for 10 minutes. After demolding, a 5 mm metal graphite material plate was obtained. The pressed metal graphite plate was cut into 50×50 mm plates.
[0047] (2) Graphite fluoride and resin mixed and soaked:
[0048] Take 30g of phenolic resin HY-918, 50g of epoxy resin E-44 and 20g of polyester resin 197C, stir and blend the above substances to obtain a glue injection agent;
[0049] Fix the metal fluoride graphite plate in a stainless steel impregnation barrel with a clamp, keep the vacuum degree in the barrel at 0.1MPa, and impregnate for 1 hour. Then put the injection agent into the impregnation barrel, and keep it at a specific impregnation pressure of 0.6MPa for 40-50min. The resin system penetrates into the gaps of the flexible graphite plate to obtain a metal fluoride graphite plate impregnated with resin. Clean the mixed resin remaining on the surface of the impregnated metal fluoride graphite plate with isopropyl alcohol.
[0050] Under argon atmosphere, the impregnated and cleaned metal fluoride graphite plate was heat-cured in a tubular furnace, with the temperature rising from room temperature to 300°C at a heating rate of 5°C / min and kept warm for 30 minutes to ensure sufficient flow of the resin in the composite bipolar plate, thereby preparing a graphite composite material plate.
[0051] Example 2
[0052] A graphite composite material plate, which is otherwise the same as Example 1, and differs from Example 1 in that the mass ratios of the phenolic resin, the epoxy resin and the polyester resin are different, as follows:
[0053] Take 20g of phenolic resin HY-918, 50g of epoxy resin E-44 and 30g of polyester resin 197C and stir and blend them.
[0054] Example 3
[0055] A graphite composite material plate, which is otherwise the same as Example 1, and differs from Example 1 in that the mass ratios of the phenolic resin, the epoxy resin and the polyester resin are different, as follows:
[0056] Take 30g of phenolic resin HY-918, 40g of epoxy resin E-44 and 30g of polyester resin 197C and stir and blend them.
[0057] Example 4
[0058] A graphite composite material plate, which is otherwise the same as Example 1, and differs from Example 1 in that the mass ratios of the phenolic resin, the epoxy resin and the polyester resin are different, as follows:
[0059] Take 40g of phenolic resin HY-918, 30g of epoxy resin E-44 and 20g of polyester resin 197C and stir and blend them.
[0060] Example 5
[0061] A graphite composite material plate, which is the same as Example 1 in other aspects, and differs from Example 1 in that the mass ratios of phenolic resin, epoxy resin and polyester resin are different, as follows:
[0062] Take 30g of phenolic resin HY-918, 60g of epoxy resin E-44 and 10g of polyester resin 197C and stir and blend them.
[0063] Comparative Example 1
[0064] A graphite composite material plate, which is the same as Example 1 in other aspects, but different from Example 1 in that the pressed metal graphite plate is not subjected to resin impregnation treatment, and a 50×50 mm plate is directly cut out, washed with pure water, and dried to obtain a 5 mm thick graphite metal plate.
[0065] Application Examples
[0066] Application Example 1
[0067] An electrosynthesis process for succinic acid is carried out according to the following steps:
[0068] The membrane-free electrosynthesis of succinic acid uses the graphite composite plate of Example 1 as the anode material, stainless steel as the cathode, 1 mol / L sulfuric acid as the supporting electrolyte, and the concentration of maleic acid is 1.5 mol / L, and electrolysis is performed at a temperature of 60-70°C; after the electrolyte flowing out of the electrolytic cell is cooled to room temperature, succinic acid crystals can be precipitated, and the product is obtained after filtering and drying. The graphite composite plate prepared by the present invention has excellent electrochemical performance, the yield of succinic acid is greater than 75%, and the total current efficiency is greater than 70%.
[0069] Application Example 2-5
[0070] A process for electrosynthesis of succinic acid, compared with Application Example 1, differs in that the raw materials used in the anode of the electrolytic cell are different, as follows:
[0071] In Application Example 2, the electrolytic cell anode uses the graphite composite material plate prepared in Example 2;
[0072] In Application Example 3, the anode of the electrolytic cell adopts the graphite composite material plate prepared in Example 3;
[0073] In Application Example 4, the anode of the electrolytic cell adopts the graphite composite material plate prepared in Example 4;
[0074] In Application Example 5, the anode of the electrolytic cell adopts the graphite composite material plate prepared in Example 5;
[0075] Application Comparative Example 1
[0076] A succinic acid electrosynthesis process, compared with Application Example 1, the difference lies in that the raw materials used in the electrolytic cell anode are different, specifically as follows: the electrolytic cell anode in Application Comparative Example 1 uses the graphite composite material plate prepared in Comparative Example 1;
[0077] Performance testing
[0078] 1. Electrochemical performance test of graphite composite plates
[0079] 1. Detection of current efficiency: the ratio of the mass of succinic acid synthesized in the electrolytic cell per unit time to the theoretical output calculated by Faraday's law; wherein the mass of succinic acid synthesized in the electrolytic cell per unit time is obtained from the application example.
[0080] In Application Examples 1-5 and Comparative Example 1, the current efficiency test results of the graphite composite plate are shown in Figure 2 .
[0081] 2. Performance testing of graphite composite plates
[0082] 1. Service life: Using the graphite composite plates of Examples 1-5 and Comparative Example 1 as anodes and the stainless steel plates as cathodes, at 2A / cm 2 A 1.0 mol / L sulfuric acid solution was electrolyzed at 60°C with a high current density DC regulated power supply. The initial cell voltage was relatively stable, but after a period of time, when the cell voltage rapidly increased to a difference of more than 10V compared with the initial voltage, it indicated that the electrode had failed. The time it took for the electrode to fail was the accelerated service life of the electrode.
[0083] The service life test results are shown in Figure 3 .
[0084] 2. Bending strength: According to GB / T 20042.6-2011 standard, the bending strength of the graphite composite plate (prepared in Examples 1-5 and Comparative Example 1) was measured by three-point bending using a mechanical testing machine at a loading speed of 0.5 mm / min. The middle and edge of the sample were measured three times to obtain the average value.
[0085] The bending strength test results are shown in Figure 4 .
[0086] It can be seen from Examples 1-5 and Comparative Example 1, Application Examples 1-5 and Application Comparative Example 1 in combination with Table 1-3 that Application Comparative Example 1 uses traditional graphite as the anode material. Compared with Application Example 1, the reaction current efficiency of Application Comparative Example 1 is significantly reduced, and the service life and bending strength are also lower than those of Application Example 1. Therefore, ordinary graphite materials not only lead to a decrease in electrochemical performance during synthesis, but also other properties are not as good as those of graphite composite materials.
[0087] By modifying the graphite material according to different proportions of resin, it can be seen that different resins have different performance. When the ratio of phenolic resin to epoxy resin is large, the bending strength of the graphite composite plate is the largest; and when the polyester resin is more, the corrosion resistance of the graphite composite plate is the best.
[0088] It should be noted that the above content only illustrates the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications all fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a graphite composite electrode, characterized in that: The following steps are involved: (1) drying the fluorinated graphite in an oven, placing the dried fluorinated graphite in a ball mill, adding aluminum and lead metals, and performing synchronous ball milling mixing, the speed of the ball mill is 100 to 300 rpm, the ball milling time is 1 to 4 hours, the mass ratio of the grinding medium ceramic ball to the mixed powder is 1 to 5:1, the filling rate of the ball mill drum is 30% to 50%, and a uniformly distributed mixed powder is obtained, and the mixed powder is pressed into a metal fluorinated graphite plate with a thickness of 1 to 5 mm; (2) Blending phenolic resin, epoxy resin and polyester resin to obtain a sizing agent; immersing the metal fluoride graphite plate in the sizing agent, and after curing, washing and drying, obtaining a graphite composite material electrode.
2. The method for preparing a graphite composite material electrode according to claim 1, characterized in that: In step (1), the mixed powder is pressed into a metal fluoride graphite plate, which specifically includes the following steps: the mixed powder is placed in a molding tool, first pre-pressed at a pressure of 1 to 2 MPa for 30 seconds to discharge the gas in the powder, and then formally pressed at a pressure of 10 MPa for 10 minutes, and the metal fluoride graphite plate is obtained after demolding.
3. The method for preparing a graphite composite material electrode according to claim 1, characterized in that: In step (1), the mass ratio of graphite fluoride, aluminum and lead is 8-9:1-2:1-2.
4. The method for preparing a graphite composite electrode according to claim 1, characterized in that: In step (1), the content of the fluorinated graphite is 90-99% and the sheet diameter is 1-10 μm.
5. The method for preparing a graphite composite material electrode according to claim 1, characterized in that: In step (2), the mass ratio of the phenolic resin, the epoxy resin and the polyester resin is 2-5:3-7:2-4.
6. The method for preparing a graphite composite electrode according to claim 1, characterized in that: In step (2), the impregnation treatment includes the following steps: placing the metal fluoride graphite plate in an impregnation barrel, maintaining the vacuum degree at 0.1 MPa, impregnating for 1 hour, then adding the injection agent into the impregnation barrel, and maintaining the impregnation pressure at 0.3-0.8 MPa for 40-50 minutes.
7. The method for preparing a graphite composite material electrode according to claim 1, characterized in that: In step (2), curing includes the following steps: in an argon atmosphere, the temperature of the tubular furnace is raised to 300° C. at a heating rate of 3.0 to 5.5° C. / min, and the temperature is kept at this temperature for 30 minutes.
8. A graphite composite electrode prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the graphite composite material according to claim 8 in the electrosynthesis of succinic acid.
